Functional Traits of Fish Species: Adjusting Resolution to Accurately Express Resource Partitioning - da Silva, Victor E. L.; Silva-Firmiano, Luana P. S.; Teresa, Fabrício B.; Batista, Vandick S.; Ladle, Richard J.; Fabré, Nidia N. (Frontiers in Marine Science, 2019)
Trait-based community descriptors have been widely used to make inferences about community assembly processes. The level of traits discrimination (measurement resolution) can have consequences for how good diversity patterns correlate with predictor variables. Here, we develop a novel framework to evaluate: i) how much information is lost when the measurement resolution of functional traits is lowered, and; ii) to what extent morphological traits and phylogeny can be used as surrogates of feeding strategy. We also tested whether measurement resolution of traits affects the ability of community functional diversity metrics to discriminate different habitats. We used empirical data from marine fish communities and correlated pairwise dissimilarities based on the most detailed measurement resolution of diet with pairwise dissimilarities based on different resolutions of diet, ecomorphology, and phylogeny. We then compared functional diversity between three marine regions using the different feeding trait resolutions, phylogeny and ecomorphology to detect environment filtering. Phylogeny and ecomorphological traits were not correlated with fish diet. There was a strong correlation between the highest and second highest measurement resolution, with the association decaying for lower resolution data. Significantly, high-resolution data are better able to discriminate different habitats than functional diversity. These results do not support the use of surrogates for trophic traits and highlight the importance of measurement resolution in studies of functional diversity in tropical marine ecosystems